2009
DOI: 10.1007/s00330-008-1252-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced CT imaging of hepatocellular carcinoma in cirrhosis: feasibility of a prolonged dual-phase imaging protocol with tracer kinetics modeling

Abstract: Dynamic contrast-enhanced (DCE) CT imaging of four patients with hepatocellular carcinoma (HCC) was performed using a dual-phase imaging protocol designed with initial rapid dynamic imaging to capture the initial increase in contrast medium enhancement in order to assess perfusion, followed by a delayed imaging phase with progressively longer intervals to monitor subsequent tissue enhancement behaviour in order to assess tissue permeability. The DCE CT images were analysed using a dual-input two-compartment di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Arterial blood flow was high with a sensitivity and specificity of detection of 86% and 65% within 11 weeks of tumour induction even though only 7% was visible by eye [38]. A small number of singlecentre human studies have shown the feasibility of DCE CT in HCC for detection and vascular response assessment [39][40][41][42][43][44][45][46][47]. HCC typically shows an increase in arterial liver perfusion (Fig.…”
Section: Assessment Of Tumour Vascularizationmentioning
confidence: 99%
“…Arterial blood flow was high with a sensitivity and specificity of detection of 86% and 65% within 11 weeks of tumour induction even though only 7% was visible by eye [38]. A small number of singlecentre human studies have shown the feasibility of DCE CT in HCC for detection and vascular response assessment [39][40][41][42][43][44][45][46][47]. HCC typically shows an increase in arterial liver perfusion (Fig.…”
Section: Assessment Of Tumour Vascularizationmentioning
confidence: 99%
“…However, the interstitial compartment (EES) may have a larger radial dimension (compared with its axial dimension) without a radial concentration gradient, and can be regarded as largely homogeneous. The impulse residue function for DP2 model can be given by two physiologic phases (63)(64)(65)(66)(67)(68)(69):…”
Section: Distributed Parameter (Dp) Models and Variationsmentioning
confidence: 99%
“…Also, by setting E or PS ¼ 0, the single-(vascular) compartment DP model, R DP1 (t), is simply given by R p (t). The physiological meaning of the two transport phases can be explained as follows (63)(64)(65)(66)(67)(68)(69). During the initial vascular transit phase 0<t<t p , R p (t) is a constant (unity) reflecting the fact that the total amount (100%) of tracer in the injected bolus is residing in the tissue, although a portion of the tracer could diffuse from the IVPS into EES.…”
Section: Distributed Parameter (Dp) Models and Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible to get relevant information only if data are correctly registered. Two main approaches are possible to deal with respiratory motion, sequential breath hold [1] or free-breathing. In the present study, free breathing is selected, since a less stressed patient usually provides sequences with more regular motion.…”
Section: Introductionmentioning
confidence: 99%